Growth hormone receptor promotes osteosarcoma cell growth and metastases. Issue 1 (18th December 2019) - Cheng, Mo; Huang, Wending; Cai, Weiluo; Fang, Meng; Chen, Yong; Wang, Chunmeng; Yan, Wangjun
Abstract : Osteosarcoma (OS) is the primary bone malignancy in children and adolescents, with a high incidence of lung metastasis and poor prognosis. Here, we report that growth hormone receptor (GHR) is overexpressed in OS samples compared with osteofibrous dysplasia. We subsequently demonstrated that GHR knockdown inhibited colony formation, promoted cell apoptosis and decreased the number of cells at G2/M phase in 143B and U2OS cells. Furthermore, knockdown of GHR inhibited tumor growth in vivo . Together, these findings indicate that GHR modulates cell proliferation and metastasis through the phosphoinositide 3‐kinase/AKT signaling pathway and may be suitable for use as a putative biomarker of OS. Abstract : Here, we demonstrate that growth hormone receptor knockdown inhibits colony formation, promotes cell apoptosis and decreases the number of cells at G2/M phase in 143B and U2OS cells. Furthermore, knockdown of growth hormone receptor inhibits tumor growth in vivo .